Three new species of freshwater Macrostomum (Platyhelminthes, Macrostomida) from southern China - Sun, Ting; Zhang, Lv; Wang, An-Tai; Zhang, Yu (Zootaxa, 2015)
Macrostomum is a diverse genus of turbellarians with more than 180 species described from around the world. However, the Macrostomum fauna in China is poorly known. In this study, three new species of freshwater Macrostomum were described from southern China based on morphology of the penis stylet, an important character for species identification in this genus. In M. heyuanensis n. sp., the penis stylet bends 108° leftwards at its 1/2 length then backwards besides the distal opening, and the terminal region is thicker than other parts of penis stylet. In M. dongyuanensis n. sp., the penis stylet is J-shaped, with the opening at the tail end. In M. bicaudatum n. sp., the penis stylet is C-shaped, with the upper margin of the distal end longer but slimmer than the lower margin. In addition, molecular phylogenetic analyses were conducted to aid the classification of the novel species. Finally, their habitat and taxonomic status are compared and discussed.